Social and Behavioural Change Communication Challenges, Opportunities and Lessons from Past Public Health Emergencies and Disease Outbreaks: A Scoping Review - Laston Gonah; Sibusiso Cyprian Nomatshila (Annals of Global Health)
Background: Documentation of social behavioural change communication (SBCC) regarding challenges, opportunities and lessons drawn from past public health emergencies is worthwhile to inform priorities for future response efforts. Aim: The aim of this review is to scope the evidence on social behavioural change communication regarding challenges, opportunities and lessons drawn from Ebola, coronavirus disease 2019 (COVID-19), monkeypox and cholera outbreaks from studies published before March 2024, and suggest priorities for future response efforts. Methods: A Boolean strategy was used to search electronic databases for relevant published articles, complemented by relevant studies identified from reference lists. Results: The challenges, opportunities, lessons learnt and priorities for SBCC were consistent across study contexts, showing marked variations over time. The significance of technology, infodemic management, and behavioural data generation emerged more frequently and became increasingly important over time. Identified challenges were uptake hesitancy, limited capacity to undertake infodemic management, inadequate funding and human resources for SBCC, competing priorities, parallel or conflicting interventions due to inadequate coordination, difficulties evaluating SBCC programmes and missed opportunities for integration into routine programmes. Existing supportive structures for SBCC, strong political will and participation, as well as rapid information exchange enabled by technological advancement, represented opportunities for enhancing the effectiveness of SBCC programmes. Key lessons were that a multisectoral approach and coordination, partnership and active collaboration amongst stakeholders; building/strengthening trust, target population segmentation and localization of interventions, are important for enhancing the effectiveness of SBCC programmes. Political will, involvement and participation represent the core of social behavioural change (communication) interventions during a public health emergency. Conclusion: SBCC programming for future response to public health emergencies and disease outbreaks should consider the diverse assortment of benefits, threats/challenges and opportunities brought about by technology, infodemics and behavioural data generation to be more effective.